Microplastics in the Arctic: a transect through the Barents Sea - Emberson-Marl, H.; Coppock, R. L.; Cole, M.; Godley, B. J.; Mimpriss, N.; Nelms, S. E.; Lindeque, P. K. (Frontiers in Marine Science, 2023)
Globally, the abundance of microplastics in our oceans is increasing, including within the remote locations of the polar regions. The Barents Sea, which adjoins the Arctic Ocean, is an area of high primary productivity that, owing to the convergence of regional currents, has been mooted as a potential sixth ocean gyre that may coalesce high concentrations of plastic debris. This study aimed to explore data collected from large volume samples of sub-surface water collected from transects through the Barents Sea to quantify and characterise microplastics in this region, with a focus on potential impacts to zooplankton. Overall, the mean microplastic abundance in the Barents Sea was 0.011 microplastics m-3 (range: 0.007 – 0.015 m-3). Microplastics were found in higher abundances nearer land mass at the southern end of the transect and northwards towards the ice edge, recording 0.015 microplastics m-3 during both transect legs. Microplastics were predominantly fibrous (92.1%) and typically blue (79%) or red (17%) in colour. A range of polymers were identified including polyester (3.8%), copolymer blends (2.7%), elastomers (7.1%) and acrylics (10.6%), however semi-synthetic polymers dominated, comprising 74.4% of particles found. Higher microplastic concentrations in the northernmost transect may stem from melting sea-ice, while the higher concentrations in the southernmost transect likely derive from the long-range transport of microplastics via currents from Europe.